Exploring the use of knowledge management practices in an academic library in a changing information environment - Judith Mavodza; Patrick Ngulube (South African Journal of Libraries and Information Science, 2011)
Some academic libraries have significantly developed and are applying some knowledge management (KM) principles and practices in the provision of library services. KM has been implemented in commercial and business environments towards achieving operational advantages. Its principles and tools can help libraries to improve performance and fulfil their mandate. By using a case study approach, the objective of this research was to find out how knowledge is identified, captured, shared and retained in order to enhance performance and improve the quality of service in the Metropolitan College of New York (MCNY) library. A web-based questionnaire, some institutional documents, observation and face-toface interviews were used to collect data. Data was analysed both quantitatively and qualitatively. The findings indicate that the MCNY library practices are not deliberately informed by KM principles, but are amenable to KM principles. It is recommended that KM, with its potential to turn individual knowledge into organisational knowledge, should be used in positioning the MCNY library in a changing information environment.